Mannich base limits Candida albicans virulence by inactivating Ras-cAMP-PKA pathway. Issue 1 (December 2018) - Rajasekharan, Satish; Kamalanathan, Chakkaravarthi; Ravichandran, Vinothkannan; Ray, Arvind; Satish, Ann; Mohanvel, Sucharitha
Abstract Mannich bases and its derivatives are regarded as supreme pharmacophores in therapeutics. The study investigates the antimycotic potential of Mannich bases, 1-((1H-benzimidazol-1-yl) methyl) urea (C1) and 1-((3-hydroxynapthalen-2-yl) methyl) thiourea (C2), againstCandida albicans . Biofilm and hyphal inhibitory activities of the Mannich bases were tested by crystal violet quantification, fluorescence imaging cAMP rescue, qRT PCR, and by molecular docking analysis. The compounds inhibited the biofilms ofC. albicans and restrained the filamentation abilities of the pathogen. Structure-activity relationship studies revealed that the presence of urea or thiourea moiety in the tail section is essential for interacting with adenylate cyclase (AC). The Mannich bases seemed to block Ras-cAMP-PKA pathway by inhibiting second messenger activity required for hyphal induction and biofilm formation. In conclusion, the study warrants point-of-care testing of C1/C2 and provides a starting point for deriving several structurally modified Mannich bases which might plausibly replace the prevailing antimycotic drugs in future.